On symmetries of crystals with defects related to a class of solvable groups (S1) - Nicks, Rachel; Parry, Gareth P. (Sage, 2012)
We consider distributions of dislocations in continuum models of crystals which are such that the corresponding dislocation density tensor relates to a particular class of solvable Lie group, and discrete structures which are embedded in these crystals. We provide a canonical form of these structures and, by finding the set of all generators of a corresponding discrete subgroup, we determine the ‘material’ symmetries that constrain appropriate strain energy functions.